Realization and contribution of restaurant tax revenue to local own-source revenue in Madiun - Ayu Chairina Laksmi; Izzalya Alfa Safina ‘Ad’n (Proceeding International Conference on Accounting and Finance, 2025)
This study aims to analyze the realization and contribution of Restaurant Tax to Local Own-Source Revenue (Local Revenue) in Madiun, and identify efforts made by the Regional Revenue Agency (Bapenda) in increasing Restaurant Tax revenue. Based on the data from 2019 to 2023, the contribution of Restaurant Tax to Local Own-Source Revenue in Madiun is still relatively small, with an average annual contribution of 1.01%. Although the effectiveness level of this tax is classified as very effective, its contribution to Local Own-Source Revenue has not been maximized. Some of the inhibiting factors include lack of taxpayer compliance and geographical challenges in restaurant monitoring. To overcome these obstacles, Bapenda Madiun makes efforts such as socialization, monitoring, and the application of the "Si Kampung" application to facilitate taxpayers in calculating and paying taxes. The findings of this study indicate that optimizing Restaurant Tax revenue can increase Local Own-Source Revenue contributions in a sustainable manner.